The Desıgn and Development of Dıfferentıated Mathematıcs Teachıng Modules Based on Multıple Intellıgence - Azin Taufik; Nuranita Adiastuty (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2024)
Differentiated learning is becoming increasingly important in the world of education because each student has different characteristics and learning needs. Students have different backgrounds, experiences, interests, and intelligence, such as visual-spatial, verbal-linguistic, logical-mathematical, bodily-kinesthetic, musical-rhythmic, interpersonal, and intrapersonal intelligence. Multiple intelligence is a theory that states that each individual has several different types of intelligence or intelligence. Every individual has unique and different multiple intelligences. This research aims to obtain a differentiated mathematics learning tool based on multiple intelligences that meets valid and practical criteria. The learning tool in question is a Learning Implementation Plan which was developed according to the principles of differentiated learning based on multiple intelligences. The design used in this research is Research and Development. The stages or procedures of this development research refer to five main steps, namely needs analysis; product development (teaching materials); expert validation and product revision, and small-scale field trials. Data collection techniques use interviews, questionnaires, observations, and validation sheets. The results of the expert validation analysis of the RPP are included in the very valid criteria with an average validity value of 3.88 and the results of the response analysis obtained a score of 90.10 with very practical criteria. Differentiation in this research is based on the multiple intelligences of diverse students, researchers or teachers can continue research by looking at differentiation from other relevant aspects